The effect of prenatal yoga on maintaining the childbirth process in a physiological state in Indonesian mothers - Rohaya Rohaya; Murdingsih Murdiningsih; Yunetra Franciska; Siti Hindun; Ocktariyana Ocktariyana (Journal of Research Development in Nursing and Midwifery)
Background: Yoga is a non-pharmacological intervention that enhances maternal strength and flexibility while improving the mother's capacity to adapt to physiological changes and labor responses. This study aimed to evaluate the effect of prenatal yoga on the duration of the first, second, and third stages of labor, as well as blood volume during the fourth stage of labor. Methods: A quasi-experimental study was conducted involving 92 pregnant women in their third trimester who presented no complications and exhibited low-risk factors. The participants were assigned to either the yoga intervention group or the control group using a simple random sampling method. The intervention group engaged in yoga sessions lasting 30 min, conducted over eight weeks, beginning at 30 weeks of gestation. In contrast, the control group received routine standard care without any yoga intervention. The durations of the first, second, and third stages of labor as well as blood volume during the fourth stage, were analyzed between the intervention and control groups using independent t-test and Mann-Whitney U test, with a significance level of p <0.05. Results: The study revealed a significant difference in the duration of the first (p=0.004) and second stages (p=0.0001) of labor, as well as in the bleeding volume during the fourth stage of labor (p=0.0001) between the yoga intervention group and the control group. However, no significant difference was observed in the duration of the third stage of labor (p=0.234). Conclusion: Prenatal yoga during the third trimester of pregnancy may help maintain physiological conditions during the first and second stages of labor and reduce the risk of bleeding.